Merchandising and its impact on consumer behavior - Kapinus, Larisa; Skryhun, Natalya (My University, 2013)
The article is described the various approaches to the definition of merchandising, studied the merchandising tool that influences on the consumer behavior in a shop, proved the need for a merchandising point of sale technology.
Keywords: merchandising; point of sale; consumer behavior; мерчандайзинг; точка продажу; поведінка споживачів; мерчандайзинг; точка продаж; поведение потребителей; кафедра маркетингу